A Mathematical Study on the System of Partial Differential Equations Describing Reverse-Flow Reactor - Edy Wibowo, Ratno Bagus; Suzuki, Takashi; Takahashi, Ryo (Mathematical Modelling and Analysis, 2016)
The RFR (reverse flow reactor) has been widely studied for abatement of lean methane emission from coal mining or natural gas piping system. We show a global-in-time existence of the solution to a nonlinear system of partial differential equations modeling RFR.